Impairment of oligodendrocyte lineages in spinal muscular atrophy model systems. Issue 5 (20th March 2019) - Ohuchi, Kazuki; Funato, Michinori; Ando, Shiori; Inagaki, Satoshi; Sato, Arisu; Kawase, Chizuru; Seki, Junko; Nakamura, Shinsuke; Shimazawa, Masamitsu; Kaneko, Hideo; Hara, Hideaki
Abstract : Survival motor neuron (SMN) deficiency indicates that various cellular processes are impaired in spinal muscular atrophy (SMA). Previous reports have shown that SMN deficiency causes motor neuron degeneration, whereas the numbers of astrocytes and microglia are significantly increased or activated in SMA model systems. Only a few groups have studied the role of oligodendrocyte (OL) lineages such as OL precursor cell and nerve/glial antigen 2 (NG2)-glia in SMA pathology. Our aim in this study was to investigate whether OL lineages are impaired in SMA model systems. We investigated the expression of myelin basic protein (MBP) and NG2, which are OL lineage markers, using SMNΔ7 mice ( mSmn −/−, SMN2 +/+, SMNΔ7 +/+ ) and cell cultures derived from induced pluripotent stem cells generated from SMA patients. We showed for the first time that the OL lineages, including NG2-positive OL precursor cells and MBP-positive myelinating OLs were impaired in SMNΔ7 mice and induced pluripotent stem cells derived from SMA patients. Notch was involved in the decline of NG2 expression in the spinal cord of SMNΔ7 mice. In addition, pharmacological Notch inhibition promoted MBP-positive OL differentiation in SMNΔ7 mice. These findings indicate that OL differentiation was impaired in SMA, which might be involved in the Notch dysregulation.